Gulag : a history - Applebaum, Anne (Anchor Books, 2004)
In this magisterial and acclaimed history, Anne Applebaum offers the first fully documented portrait of the Gulag, from its origins in the Russian Revolution, through its expansion under Stalin, to its collapse in the era of glasnost.